Self-Esteem and Working Capacity of Women after Mastectomy - Maria Garus (Human Research in Rehabilitation)
The study aimed to examine the impact of mastectomy on women's self-esteem and labour adaptation. The research was conducted using data collected in 2022 and 2023 from 11 women aged 18 and older who had undergone mastectomy. The methodology involved questionnaires and in-depth individual interviews, focusing on the physical, psychological, social, and professional aspects of patients’ lives to assess their needs and develop rehabilitation programmes. The findings indicate that mastectomy significantly affects women's mental and physical well-being, leading to a decreased quality of life and reduced work capacity, thereby necessitating specialised rehabilitation programmes to address physical limitations and enhance psychological resilience. Women who undergo breast reconstruction and receive adequate social support exhibit better psychosocial well-being and labour adaptation. Participation in the rehabilitation programme has led to an increase in the percentage of women who have positively assessed their self-esteem.